Haemoglobin revisited: delineating population structure with the world’s first molecular genetic marker used in fisheries research - Bjørghild Breistein; Geir Dahle; Torild Johansen; Per Erik Jorde; Kevin A. Glover (Royal Society Open Science)
When haemoglobin genotyping was implemented in the early 1960s to investigate population genetic structure in Atlantic cod (Gadus morhua), it became one of the first molecular genetic markers deployed in fisheries research worldwide. However, its suitability was questioned due to its potential for selection. While the issue of neutrality concerned the first population geneticists, markers under selection are now routinely used to study population genetic structure. Here, we revisited haemoglobin genotyping half a decade later to analyse >6000 mature Atlantic cod from 73 spawning locations throughout Norway’s approximately 2500 km coastline. A latitudinal gradient in allele frequencies, with a decrease in the HbI-2 allele towards the south, was observed. Our observed HbI-2 frequencies were consistently slightly lower than data from the 1960s, potentially reflecting adaptive changes to increasing sea temperatures. However, despite this difference, the observed north–south pattern in allele frequencies observed here and in the historical studies overlapped, aligning with current knowledge of population genetic structure in this species. We therefore conclude that this once questioned marker, which provided the first molecular genetic insights into genetic structure in Atlantic cod, provides knowledge consistent with the isolation by distance pattern revealed through decades of research in this species in this region.